Effects of supplementation with increasing levels of energy concentrate on the productive response and ruminal digestion of dairy cows grazing lucerne pasture - Salado, Eloy Eduardo; Bretschneider, Gustavo; Cuatrin, Alejandra; Gagliostro, Gerardo Antonio (Scientific Research, 2018)
The aim of the study was to determine the effect of three levels of energy concentrate intake on dry matter (DM) and energy intake, milk yield and composition, rumen environment and pasture neutral detergent fiber (NDF) digestion. Twelve Holstein multiparous cows in early lactation (69.0 ± 5 days postpartum) producing 32.8 (±4.0) kg milk were assigned to three treatments at (kg/cow day) 3.5 (T3.5), 7.0 (T7.0) and 10.5 (T10.5) kg concentrate in a 3 × 3 Latin Square design. Parameters of ruminal environment and neutral detergent fiber (NDF) digestion were obtained using 3 additional rumen cannulated cows. Concentrate was composed (as fed) by corn grain (68%), soybean meal (22%), wheat bran (8%) and a vitamin-mineral premix including monensin and thoroughly consumed. Yields (kg/cow day-1) of milk, 4% fat corrected milk (4% FCM 4%) and energy corrected milk (ECM) resulted higher (p < 0.05) in T7.0 (29.6, 26.1 and 25.7) compared to T3.5 (27.7, 24.5 and 24.2) but similar to those obtained in T10.5 (30.6, 26.2 and 26.0). Milk protein yield increased linearly (p < 0.01) from 0.82 to 0.92 kg/cow day-1 without effects on yield of milk fat. Concentrations (g/100 g) of milk fat (3.19), protein (2.97), total solids (11.75), non-fat solids (8.60) and casein (2.40) did not differ. Milk lactose content (g/100 g) was linearly increased (p < 0.02) from 4.91 to 4.98 whereas milk urea decreased (p < 0.01) from 0.048 to 0.043. Intakes of DM and energy increased with concentrate level without effects on conversion efficiency. Changes in live weight (LW), body condition score (BCS) and concentrations of plasma non-esterified fatty acids (NEFA), glucose, insulin, somatotrophin (GH) and insulin-like growth factor (IGF-I) were not affected. Plasma urea levels resulted lower (p < 0.05) in T10.5. Ruminal pH and ammonia nitrogen (N-NH3) resulted lower (p < 0.05) in T10.5 compared to T3.5. Concentration of total volatile fatty acids (VFA) was higher (p < 0.05) in T3.5 due to the increase in acetate and butyrate while the acetate: Propionate ratio remained unchanged. Pasture NDF digestion was affected as concentrate intake increased. To increase milk protein yield and reduce concentrations of N-NH3 in rumen and milk, feeding an energy concentrate at 41% of total DM intake resulted an effective tool.